A PAH-degrading bacterial community enriched with contaminated agricultural soil and its utility for microbial bioremediation. (August 2019) - Lu, Chao; Hong, Yang; Liu, Juan; Gao, Yanzheng; Ma, Zhao; Yang, Bing; Ling, Wanting; Waigi, Michael Gatheru
Abstract: A bacterial community was enriched with polycyclic aromatic hydrocarbons (PAHs) polluted soil to better study PAH degradation by indigenous soil bacteria. The consortium degraded more than 52% of low molecular weight and 35% of high molecular weight (HMW) PAHs during 16 days in a soil leachate medium. 16S rRNA gene high-throughput sequencing and quantitative polymerase chain reaction analyses for alpha subunit genes of ring-hydroxylating-dioxygenase (RHDα) suggested that Proteobacteria and Actinobacteria at the phylum level, Pseudomonas, Methylobacillus, Nocardioides, Methylophilaceae, Achromobacter, Pseudoxanthomonas, and Caulobacter at the generic level were involved in PAH degradation and might have the ability to carry RHDα genes ( nidA and nahAc ). The community was selected and collected according to biomass and RHDα gene contents, and added back to the PAH-polluted soil. The 16 EPA priority PAHs decreased from 95.23 to 23.41 mg kg −1 over 35 days. Compared with soil without the introduction of this bacterial community, adding the community with RHDα genes significantly decreased soil PAH contents, particularly HMW PAHs. The metabolic rate of PAHs in soil was positively correlated with nidA and nahAc gene contents. These results indicate that adding an indigenous bacterial consortium containing RHDα genes to contaminated soil may be a feasible and environmentally friendly method to clean up PAHs in agricultural soil. Graphical abstract: Image 1 Highlights: 52.0% LMW and 35.4% HMW PAHs were degraded during enrichment and domestication process. Abundance of nidA, nahAc and phe genes were 6, 083, 117, 746, and 2.40 × 10 7 copies/mL, respectively. High biodegradation rate of PAHs was observed in soil with a native bacterial consortium. PAH degradation in soil was due to increased bacteria and RHDα subunits, especially nidA and nahAc. Abstract : A bacterial community enriched from PAH-polluted soil with high contents of RHDα was suitable for soil bioremediation, without introducing foreign bacteria or chemicals.